2010
DOI: 10.4097/kjae.2010.59.s.s158
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid embolism that took place during an emergent Cesarean section -A case report-

Abstract: Amniotic fluid embolism (AFE) is a rare but fatal obstetric emergency, characterized by sudden cardiovascular collapse, dyspnea or respiratory arrest and altered mentality, disseminated intravascular coagulation (DIC). It can lead to severe maternal morbidity and mortality, but the prediction of its occurrence and treatment are very difficult. We experienced a case of AFE during emergent Cesarean section in a 40+6 weeks healthy pregnant woman, age 33. Sudden dyspnea, hypotension, signs of pulmonary edema and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…One of the ominous varieties is the amniotic fluid embolus (AFE) affecting the parturient. [13][14][15] Hypotension has been associated with all cases, yet other less-lethal causes of hypotension may initially mask the true etiology. 13 There's no diagnostic test for this syndrome, and autopsy remains the only method of definitive diagnosis for AFE despite having been studied extensively.…”
Section: Unique Aspects Of Pulmonary Emboli: Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the ominous varieties is the amniotic fluid embolus (AFE) affecting the parturient. [13][14][15] Hypotension has been associated with all cases, yet other less-lethal causes of hypotension may initially mask the true etiology. 13 There's no diagnostic test for this syndrome, and autopsy remains the only method of definitive diagnosis for AFE despite having been studied extensively.…”
Section: Unique Aspects Of Pulmonary Emboli: Varietiesmentioning
confidence: 99%
“…13 There's no diagnostic test for this syndrome, and autopsy remains the only method of definitive diagnosis for AFE despite having been studied extensively. 15 In extreme cases when oxygenation and perfusion are severely compromised and such services are available, extracorporeal membrane oxygenation or cardiopulmonary bypass can be instituted. 14,16 Initial presentation frequently includes seizure activity, respiratory failure from acute respiratory distress syndrome, and cardiovascular collapse.…”
Section: Unique Aspects Of Pulmonary Emboli: Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that the incidence of AFE ranges between 1.9 and 6.1 cases per 100,000 maternities (1). AFE has a high mortality rate ranging from 13.3-40.0% (2) with an unexpected prevalence of respiratory and circulatory failure and disseminated intravascular coagulation (DIC). The causative agents of AFE are considered to be present in the meconium.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical transmitters in the amniotic fluid, such as prostaglandins, kinins, and serotonin, as well as secondary messengers from the lung tissues released by vascular occlusion are associated with the pathogenesis of AFE. Major clinical consequences of AFE are anaphylaxis, vascular occlusion, vasoconstriction mediated by prostaglandins, and DIC (2). The risk factors for AFE include maternal age (particularly >35 years), parity, smoking, race, diabetes, multiple pregnancy, previous cesarean delivery, placenta previa, placental abruption, labor induction, mode of delivery, and manual removal of placenta (1).…”
Section: Introductionmentioning
confidence: 99%